2021
DOI: 10.4149/km_2021_2_109
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DLC films on oxynitriding-treated Vanadis 10 tool steel through the various duty cycles of DC-pulsed plasma-enhanced CVD

Abstract: In this study, DLC films were coated on oxynitriding-treated Vanadis 10 tool steel using the DC-pulsed plasma CVD technique. The experimental parameters included different duty cycles (9, 13, 17, and 21 %) with asymmetric bipolar-pulsed voltages of -3 kV, a gas flow of CH4 maintained at 15 sccm, and a deposition time of 90 min. Meanwhile, the properties of DLC films were measured by Raman spectroscopy, Rockwell indentation, wear tests, FT-IR, corrosion tests, water contact angle tests, and four-point probes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, both the lowest corrosion current (8.9×10 − 5 A•cm − 2 ) and highest polarization resistance (822.11 Ω•cm 2 ) appeared in the 325℃ sample. Our previous studies indicated that the samples with a lower corrosion current (I corr ) and a higher polarization resistance (R P ) exhibited better corrosion resistance [4,6,7], thus, the 325℃-deposited CrN lms had the best corrosion resistance. It is speculated that the above phenomenon is mainly caused by the density difference on the surface of the CrN coating (as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, both the lowest corrosion current (8.9×10 − 5 A•cm − 2 ) and highest polarization resistance (822.11 Ω•cm 2 ) appeared in the 325℃ sample. Our previous studies indicated that the samples with a lower corrosion current (I corr ) and a higher polarization resistance (R P ) exhibited better corrosion resistance [4,6,7], thus, the 325℃-deposited CrN lms had the best corrosion resistance. It is speculated that the above phenomenon is mainly caused by the density difference on the surface of the CrN coating (as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the oxynitriding process can form several kinds of nitrides (Fe 2 N, Fe 3 N and Fe 4 N) and oxides (Fe 2 O 3 and Fe 3 O 4 ), which improve the wear, corrosion and erosion properties of the alloy steels [5,6]. Notably, the oxynitriding layer can also effectively improve the adhesive strength as an intermediate layer during the duplex coating treatments [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%